2021
DOI: 10.1371/journal.pone.0255871
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for ambulatory blood pressure monitoring devices: Wrist-type or arm-type?

Abstract: Background Ambulatory blood pressure monitoring (ABPM) is important in evaluating average 24-hour blood pressure (BP) levels, circadian rhythm, sleeping BP and BP variability but many patients are reluctant to use standard ABPM devices. Methods We compared two validated ABPM devices, the BPro tonometric wrist monitor and the A&D TM-2430 oscillometric upper arm monitor, for agreement of recordings and acceptability in 37 hypertensive patients (aged 55±9 years). Results Successful BP measurements were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(37 reference statements)
0
6
1
Order By: Relevance
“…Zeng et al concluded that there were "considerable discrepancies" for individual readings between the two devices, but the wrist device was still preferable because of its convenience. 12 They did not measure the degree of agreement or disagreement.…”
Section: Example 1: Agreement Between Diastolic Bp Readings By Wrist-...mentioning
confidence: 99%
See 4 more Smart Citations
“…Zeng et al concluded that there were "considerable discrepancies" for individual readings between the two devices, but the wrist device was still preferable because of its convenience. 12 They did not measure the degree of agreement or disagreement.…”
Section: Example 1: Agreement Between Diastolic Bp Readings By Wrist-...mentioning
confidence: 99%
“…An ingenious advantage of assessing the agreement by direct use of clinical tolerance limits is that the researcher cannot avoid setting up these limits for assessing the agreement that many workers, such as Poloni et al 2 and Zeng et al, 12 do not do while using the Bland-Altman method and make a subjective assessment. Readers deserve to be informed about the clinical tolerance limits against which the agreement has been assessed.…”
Section: Direct Use Of Clinical Tolerance Limits For Assessing Clinic...mentioning
confidence: 99%
See 3 more Smart Citations